Tinjauan Komunikasi Terhadap Pelayanan Publik Berbasis Aplikasi Laporbup Kabupaten Lombok Timur - Sarusiyan, Hizbianto; Yaqinah, Siti Nurul; Syaoki, Muhammad (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research is motivated by the emergence of many public complaints in public services provided by local governments, so researchers are interested in seeing how the strategy and management carried out by Diskominfo as a service provider. This study aims to analyze how Diskominfo's strategy in providing public services through the Laporbup application. This research is a descriptive qualitative approach. The data collection techniques in this study are: interviews, observation, and documentation. The complaint handling strategy used by Diskominfo East Lombok Regency in providing public services is to provide channels or media that are easily accessible to the community so that the services provided are easier, effective, right on target in solving problems in the community. In addition, providing a polite response is a form of interaction that can give a good impression to the reporter. The government that provides services to the community is required to provide services that are easy and fast or straightforward, because the community will get its own satisfaction with the services provided by the government, especially Diskominfo Lombok Timur. In the complaint handling strategy carried out by Diskominfo, there is a comprehensive approach that is carried out by socializing to the community and related parties, especially to provide satisfaction to users. Furthermore, supported by good technology is one of the strategies to provide easy access to the community such as sms channels with the use of phone numbers that are easy to memorize and also websites that are easily accessed by the community.